(No) Problem for a Translator Bas. 3.1.44 / Nov. 123.28: Did or didn’t bishops have to pay sportulae? - Bochove, Thomas Ernst van (Tesserae iuris, 2023)
Reading the critical apparatus pertaining to Bas. 3.1.44 reveals an interpolation in the text of the underlying source of this Basilica chapter: Nov. 123.28, resulting in the question whether or not a bishop had to pay sportulae when his own private affairs were at issue: μηδέ included, or omitted from the text as a result of this interpolation. As a consequence, a translator is confronted with a dilemma: should he or she translate the interpolated text, or hold on to the text as transmitted by the manuscripts? The present study discusses and weighs the evidence pro and con adduced by Wilhelm Kroll – one of the editors of the text of the Novel – in his critical apparatus, and concludes that the transmission of the text of the Novel in the manuscripts and in the other testimonies is far too complicated to warrant Kroll’s conclusion that the inclusion of μηδέ in the text of Nov. 123.28, and in its wake in Bas. 3.1.44 is an old and manifest interpolation, and should therefore be deleted from the the text. In the case at issue, a translator should hold on to the text as handed down by the manuscripts.